Stressors and coping strategies among secondary school male students in Abha City, Saudi Arabia - Alsaleem, Safar Abadi; Al-qahtani, Abdulaziz Hassan; Al-qahtani, Essa Hasan; AlKhaldi, Yahia Mater (Frontiers in Psychology, 2024)
Background: Stress is a biological process in which exposure to stressors is associated with bad health effects, decreased ability of disease management, and a higher likelihood for disease-related complications and comorbidities. Stress has been considered the main factor in the etiology of many diseases like diabetes mellitus, cardiac diseases, and body aches for centuries. Students meet many stressful situations such as the need for success, academic demands, homesickness, and lack of social support. Coping with stress can be a leading cause in preventing psychological distress and a serious illness. Methods: A correlational cross-sectional approach was applied for the current research. The research targeted all secondary school male students in Abha City. A multistage cluster sample was applied by selecting schools and students from the Directorate of Education in Abha. Self-administered questionnaire sheets were distributed to students in their classes. The questionnaire covered students' socio-demographic data like ages, grades, parents' education and work, living conditions, and co-morbidities. Stressors to which the students were exposed were also enumerated with the degree of stress for each. Stress was assessed using the Holmes–Rahe stress inventory for youth. Coping skills were measured using the abbreviated version of the COPE Inventory. Results: The study included 324 students whose ages ranged from 15 to 20 years old with a mean age of 17 ± 0.9 years old. About 33% of the students were at first grade. Exact 44.4% of the students had no or minimal level of stress while major stress was recorded among 26.5% of the students. Totally, 77.8% of the students had moderate coping and none had high coping ability. Conclusions: the study revealed that more than half of the students had significant levels of stress and one out of each four had major stress. The most common stressors were due to the school environment and future planning. Young age, low socioeconomic status, parents' separation, and having chronic health problems were the most important determinants of stress among the students.